Evaluation of seedling resistance and marker assisted selection for leaf rust (Puccinia triticina) resistance in Pakistani wheat landraces, cultivars and advanced lines - Gavilán Figari, Isabel Milagros (2022)
Leaf rust is amongst major biotic constraints of wheat (Triticum aestivum L.) having ability to cause substantial yield reductions worldwide. A continuous exploration for novel sources of resistance is pre-requisite for its management. Objectives of study were to conduct resistance evaluation of 112 Pakistani landraces and 48 advanced lines/ cultivars at seedling stage with total 10 virulent pathotypes of leaf rust, 3 from Pakistan and 7 from U.S.A and to detect closely linked markers for Lr10, 16, 34 and 67 genes through marker-assisted selection (MAS). Findings revealed most of Pakistani landraces showed lack of resistance at seedling stage. Only 7 accessions of landraces and 11 advanced lines were found highly resistant against all pathotypes of Pakistan. Similarly, 10 advanced lines exhibited high resistance while variability in resistance was recorded for landraces against all pathotypes tested from USA. Marker-assisted selection revealed Lr genes i.e. Lr10, Lr16, Lr34 and Lr67 were present at various frequencies. Highest frequency was observed for Lr34 followed by Lr16 & Lr67 while lowest was recorded for Lr10. These genetic resources and lines identified effective against Pakistan and USA pathotypes are potential sources for improvement of leaf rust (LR) resistance and can be utilized as valuable material for breeding resistant wheat cultivars.